2004 Intern Report (Alchemy Project) - Davis, Joy-Dee (Tufts Archival Research Center, 2005)
My internship in the Democratic Republic of Congo lasted from June 1st to August 12th 2004. I was attached to the Jesuit Refugee Services. Owing to the civil unrest that have besieged the Congo, I was stranded in Europe from 1st to 9th June and therefore did not arrive in Kinshasa until June 9th 2004. Fearing the outbreak of more hostilities I made an attempt to conduct my interviews speedily.